2021
DOI: 10.1007/s42399-020-00662-w
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea Is Associated with Increased Severity of Disease in COVID-19: Systemic Review and Metaanalysis

Abstract: has become a pandemic since its emergence in Wuhan, China. The disease process was initially defined by presence of respiratory symptoms; however, it is now well studied and shown in evidence that this is a multisystem process. Involvement of gastrointestinal (GI) system has been identified, and GI symptoms can be the only presenting symptoms in some patients. Hence, it is important to identify and understand the GI symptoms associated with COVID-19 for appropriate care of patient. We conducted a systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 60 publications
1
17
3
4
Order By: Relevance
“…Some research proposed that a lack of respiratory support may cause this situation [90]. In addition, patients with diarrhoea were more likely to have severe disease; to some extent, faecal-oral transmission may result in an increasingly heavy load of the virus that exacerbates the symptoms of the illness [91]. Aggarwal et al found that pre-existing cardiovascular diseases were associated with worse outcomes among patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Some research proposed that a lack of respiratory support may cause this situation [90]. In addition, patients with diarrhoea were more likely to have severe disease; to some extent, faecal-oral transmission may result in an increasingly heavy load of the virus that exacerbates the symptoms of the illness [91]. Aggarwal et al found that pre-existing cardiovascular diseases were associated with worse outcomes among patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis, 15.47% of patients had at least one gastrointestinal symptom. 13 The sensitivity and specificity of the ANN model in this study were 94.5% and 17.4%, respectively. In other words, about 95% of patients with COVID-19 were identified by home monitoring using this ANN model.…”
Section: Discussionmentioning
confidence: 52%
“…Nonetheless, the results of a meta-analysis of the prevalence and mortality of COVID-19 patients with gastrointestinal symptoms indicate that the mortality among patients with gastrointestinal symptoms is similar to the overall mortality [ 20 ]. Another meta-analysis found conflicting results and reported that diarrhea is associated with increased severity of disease for COVID-19 [ 21 ]. Since this meta-analysis data was obtained from patients of countries presenting a high level of sanitation, it is likely that in most cases, the initial site of infection of COVID-19 patients was the respiratory system and that the infection of the digestive system was a secondary event and therefore may not contribute to lowering the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%